EFEKTIVITAS PROGRAM KREDIT USAHA RAKYAT DALAM PENGEMBANGAN USAHA MIKRO KECIL DAN MENENGAH PEGADAIAN CABANG SETIA BUDI DI KECAMATAN MEDAN SUNGGAL - Marlina, Egita; Revida, Erika (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
KUR is a government program aimed at MSMEs which is distributed by financial institutions so that KUR can strengthen business capital and accelerate the development of the real sector and empower MSMEs. This is stated in the coordinating minister for the Economy of the Republic of Indonesia Decree Number 1 of 2022 concerning Guidelines for Implementing KUR. The aim of this research is to determine the effectiveness of the people's business credit (KUR) program in developing MSMEs at the Setia Budi branch of Pegadaian in Medan Sunggal District. This research uses effectiveness indicators according to Sutrisno (2007), namely program understanding. on target, on time, achieving program goals, and real change. The results of research on the Effectiveness of the People's Business Credit Program (KUR) in the Development of UMKM Pegadaian Setia Budi Branch show that the program has not been effective as expected. In business development, MSMEs also find it difficult to experience business development. MSMEs have not experienced significant development, some MSMEs have survived but have not experienced business development.